1998
DOI: 10.1677/joe.0.1570463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of developmental changes in chicken and turkey insulin-like growth factor-II by homologous radioimmunoassay

Abstract: The development of a homologous RIA for chicken insulin-like growth factor-II (cIGF-II) and its application to investigate the developmental changes in IGF-II in the chicken and turkey are described. A double-antibody RIA has been developed using recombinantly derived cIGF-II as antigen, radiolabelled tracer and standard. Serial dilutions of chicken and turkey plasma were parallel to serial dilutions of cIGF-II standard. We have also established that acid/ethanol extraction of chicken and turkey plasma reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Circulating IGF-II levels also increased with age (1 week vs 6 weeks of age) although with less contrast. In the chicken, previous data vary from the absence of post-hatch variations (Radecki et al 1997) to a fall from hatch up to at least 50 days of age (McMurtry et al 1998). In mammalian species, during the postnatal period, results differ widely between species with almost undetectable I-hIGF-I.…”
Section: Discussionmentioning
confidence: 95%
“…Circulating IGF-II levels also increased with age (1 week vs 6 weeks of age) although with less contrast. In the chicken, previous data vary from the absence of post-hatch variations (Radecki et al 1997) to a fall from hatch up to at least 50 days of age (McMurtry et al 1998). In mammalian species, during the postnatal period, results differ widely between species with almost undetectable I-hIGF-I.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically important, IGF-I and II stimulate hepatic glycogen, RNA and protein synthesis (McMurtry et al, 1998;Lu, et al, 2007). IGFs were also found in amniotic fluid where they may play a role in regulating amino acid utilization Lu, et al, 2007).…”
Section: Control By Insulin-like Growth Factors I and Iimentioning
confidence: 99%
“…Plasma thyroxine (T 4 ) and tri-iodothyronine (T 3 ) were measured as previously described (Vasilatos-Younken et al 1997). Plasma insulin, IGF-I and IGF-II were measured as described by McMurtry et al (1983McMurtry et al ( , 1994McMurtry et al ( , 1998, and tissue IGF-I was measured as described by Rosselot et al (1995). McMurtry et al (1994) demonstrated that chicken IGF-binding proteins (IGFBPs) are acid-labile, so that interference of IGF-I detection by IGFBPs is not a problem using the indicated method of acid/ethanol extraction.…”
Section: Plasma Hormones and Metabolitesmentioning
confidence: 99%